2013
DOI: 10.4103/0971-7749.108166
|View full text |Cite
|
Sign up to set email alerts
|

Malignant otitis externa with bilateral cranial nerve involvement: Report of a unique case

Abstract: Figure 5: 99mTc-MDP bone scan in delayed phase showing diffusely increased concentration of radiotracer over the periphery of the anterior and inferior aspect of the right temporal bone How to cite this article: Saha S, Chowdhury K, Pal S, Saha VP. Malignant otitis externa with bilateral cranial nerve involvement: Report of a unique case. Indian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…More virulent strains produce collagenases and elastases, being responsible for vasculitis and cranial nerve involvement, respectively. Facial nerve is the most frequently involved [ 3 ], followed by glossopharyngeal, vague and accessory nerves [ 2 ]. Involvement of the abducent nerve is rare, and even rarer is the affection of the superior orbital fissure and optic foramen, which has only been described in 2013, by Baig et al [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More virulent strains produce collagenases and elastases, being responsible for vasculitis and cranial nerve involvement, respectively. Facial nerve is the most frequently involved [ 3 ], followed by glossopharyngeal, vague and accessory nerves [ 2 ]. Involvement of the abducent nerve is rare, and even rarer is the affection of the superior orbital fissure and optic foramen, which has only been described in 2013, by Baig et al [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The condition typically begins in the outer ear, manifesting with refractory otalgia that irradiates to the frontotemporal and parietal regions, usually worsening in intensity at night, accompanied by smelly otorrhea with purulent aspect [ 1 ]. Its extension to the skull base adds severity and results in an increased risk of cranial nerve involvement, with facial nerve palsy being the usual finding [ 2 ]. The most common etiologic agent is Pseudomonas aeruginosa , a microorganism that is unlikely to cause infections in healthy tissues, but able to initiate an infectious process through small traumatic injuries caused by iatrogenic manipulation in the external ear [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, though many authors have reported a non-predictable spread of the MOE to involve non-contagious sites belonging to separate compartments causing VI, VII, IX, X, XI, XII nerve palsies in various combinations very rarely these deficits have been thought to be due to parapharyngeal space involvement. ( Sokołowski et al., 2019 ; Conde-Diaz et al., 2017 ; Kornilenko et al., 2017 ; Saha et al., 2013 ; Kulkarni et al., 2005 ). Interestingly, only once before the index case, there has been a mention of MOE induced isolated XII nerve palsy with sparing of VII nerve ( Kasfiki et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature revealed that most of these cranial nerves deficits in MOE recover with long term antibiotics, except for the paralyzed VII nerve which shows very low propensity to recover even after decompressive surgery ( Mani et al., 2007 ; Conde-Diaz et al., 2017 ; Saha et al., 2013 ; Kulkarni et al., 2005 ; Kasfiki et al., 2013 ). However, there is some controversy surrounding the prognostic value of cranial nerve deficits in MOE, wherein some of the authors report it to be predictive of unfavorable outcomes and few others downplay its predictive ability ( Loh and Loh, 2013 ; Stern Shavit et al., 2016 ; Lee et al, 2008, 2017; Mani et al., 2007 ; Hatch et al., 2018 ; Soudry et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the infection spreads to the apex of petrous bone V and VI nerves are affected while IX, X, X nerve are affected via the jugular foramen. Except for 1 st cranial nerve all nerves can be affected 3 .In advanced stage even contralateral nerves can get affected 6 . Saha et al reported a case of MOE with PCM who required thyroplasty for vocal cord to control chronic aspiration and to improve quality of voice.…”
Section: Case Reportmentioning
confidence: 99%